The relationship between disease activity and quality of life in rheumatoid arthritis patients: a network analysis - Ruo-Wei Ma; Lin Zhu; Ming-Hui Zhang; Cui-E Li; Yu-Xuan Zhang; Bin-Bin Feng; Guo-Cui Wu (PeerJ)
Background The relationship between disease activity and quality of life (QoL) in rheumatoid arthritis (RA) patients was explored using network analysis. The focus of network analysis has recently shifted from studying individual groups to comparing the network structures of different subgroups. RA patients with depressive symptoms generally have lower QoL scores, so we compared the QoL networks of RA patients with and without depressive symptoms to test for differences. Methods QoL, depressive symptoms, and disease activity were measured using the 36-item Short-Form Health Survey (SF-36), Hospital Anxiety and Depression Scale (HADS), and Disease Activity Score 28 joints (DAS28). A flowchart was drawn to explore the relationship between disease activity and QoL. The RA patients were divided into groups with and without depressive symptoms for network comparison. Results A total of 424 patients with RA were included in this study. Disease activity was strongly associated with the PF (physical function) domain (edge weight = 0.237). The results of the network comparisons showed differences between the QoL network structures (M = 0.274, P = 0.029) and some specific edge strengths. Conclusion Disease activity is strongly associated with QoL in RA patients, especially in the domain of PF, and the structure of the QoL network changes in the presence of depressive symptoms in RA patients.